2007
DOI: 10.1038/sj.pcan.4501027
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 and NER genetic variants and sporadic prostate cancer susceptibility in African Americans

Abstract: Prostate cancer is a common malignancy that disproportionately affects African-American men. Environmental factors and variation in genes responsible for chemical and dietary carcinogen metabolism and DNA damage repair may modulate risk. Fourteen single nucleotide polymorphisms in NAT2 and four NER genes (ERCC1, XPF/ERCC4, XPG/ERCC5 and CSB/ERCC6) were genotyped in a case-control study of 254 African-American prostate cancer cases and 301 healthy controls from Washington, DC. Smoking status, BMI, age and genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
(41 reference statements)
3
34
0
Order By: Relevance
“…Our finding is consistent with those of several other studies in Indian population, American population and African Americans (Hyytinen et al, 1999;Hooker et al, 2008;Berhane et al, 2012). However, the significance of XPG rs2296147 polymorphisms in the development of prostate cancer in Chinese population is unclear.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding is consistent with those of several other studies in Indian population, American population and African Americans (Hyytinen et al, 1999;Hooker et al, 2008;Berhane et al, 2012). However, the significance of XPG rs2296147 polymorphisms in the development of prostate cancer in Chinese population is unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Berhane et al reported that polymorphism XPG rs2296147contributes to cancer risk susceptibility and can affect the development of prostate cancer in a Indian population, with a adjusted OR of 2.53 . Hyytinen et al (1999) reported that the polymorphism XPG Asp1104His plays an important role in the development of prostate cancer, while Hooker et al conducted a population-based study in United State reported no significant correlation between XPG polymorphisms and risk of prostate tumors (Hooker et al, 2008). Since these studies were conducted in different populations, it is difficult to make direct comparisons between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, disruption of this gene was related to the development of age-related macular degeneration (Tuo et al, 2006). Quite recently, genetic variations of ERCC6 have been linked to the susceptibility to various cancers, including lung cancer (Lin et al, 2008;Ma et al, 2009), breast cancer (Mechanic et al, 2006;Rajaraman et al, 2008), prostate cancer (Hooker et al, 2008), bladder cancer (Chen et al, 2007;Chang et al, 2009) and colorectal cancer Huang et al, 2006). However, the relation of ERCC6 polymorphism with gastric cancer risk is still unclear, which deserves to be further clarified.…”
Section: Research Articlementioning
confidence: 99%